The Orthodontic Treatment of a Patient with Idiopathic Root Resorption in Upper Incisors - Özge Çelik; Mustafa Ersöz; Hakan Kamalak (Galenos Yayinevi, 2015)
The aim of this case report was to present the treatment of a 14-year-old patient with anterior crossbite with idiopathic root resorption. A 14-year-old female patient referred to our clinic because of the presence of crossbite on the maxillary central incisor. The smile esthetics were compromised because of the crossbite of the maxillary right central incisor. Intraorally, the patient had an Angle Class I molar relationship on the left side, and her lower right first molar was lost because of decay. Initial cephalometric analysis showed that the ANB angle was −1.3, and the upper and lower incisor angles were105.9 and 82.3, respectively. The arch length discrepancies in the upper and lower arches were −2.9 mm and 4 mm, respectively. On radiographical examination, we noticed severe root resorptions. Hormonal tests (FT3, FT4, and TSH) were performed. The parents of the patient were informed about the root resorption. In the hematological and biochemical examinations, the patient did not show any problems. As a result of 8-month treatment, the chief complaint of crossbite was corrected in five months. The teeth were leveled and aligned. The final occlusion showed a Class I canine and molar relationship. Posttreatment radiographs showed that the pretreatment maxillary incisors' root resorption was at the same level. A satisfying occlusion and esthetic were achieved. Orthodontic treatment of the teeth with idiopathic root resorption can be achieved using proper mechanics and optimum force.